Obtaining the selected surface roughness by means of mathematical model based parameter optimization in abrasive waterjet cutting - Perec, Andrzej (Strojniški vestnik, 2017)
The study on the effect of abrasive water jet machining process parameters on micro alloyed steel surface roughness was described. Taguchi method to predict machining parameters of due to minimum surface roughness was used. The influence of pressure, abrasive flow rate and traverse speed on the Rz and Rmax roughness parameters were presented. The optimum combination of processing parameters was established. Verified parameters were tested and the achieved results were compared to predicted values. This method allows limiting the amount of research needed to achieve the desired test results, thereby reducing the time as well as the cost required to carry them out. The Taguchi signal/noise (S/N) ratio enables the assessment of the relevance of the impact of various parameters on the process, which is still not well enough understood.
Keywords: abrazivni vodni curek; načrtovanje eksperimentov; napovedovanje; optimizacija; rezanje